CULTURE SHOCK PHENOMENON IN NORTH SUMATERA STATE ISLAMIC UNIVERSITY COMMUNICATION SCIENCE STUDENTS - Putri Kiara Fitria; Syavira Adisti; Gilang Adjie Prayudha (OPINI: Journal of Communication and Social Science, 2024)
The culture shock phenomenon poses a significant challenge for Communication Science students at the North Sumatra State Islamic University (UINSU) as they navigate a diverse educational environment. This study rigorously examines students' experiences in managing complex cultural differences within the campus setting. Employing a descriptive qualitative approach, we thoroughly investigate the factors influencing culture shock, such as language disparities, social norms, and cultural values. In-depth interviews with Communication Science students from outside North Sumatra yield valuable insights into their adaptation to the new environment. Our research definitively identifies students' diverse emotional, cognitive, and behavioral reactions to culture shock, encompassing stress, anxiety, and a sense of isolation. Students frequently grapple with difficulties in comprehending and communicating different social norms and local customs. However, our findings underscore the resilience of many students who, through peer support and their own adaptive strategies, effectively acclimate to their new environment.